Blind tiger - Brown, Sandra, 1948- (Grand Central Publishing, 2021)
"Thatcher Hutton, a war-weary soldier on the way back to his cowboy life, jumps from a moving freight train to avoid trouble . . . and lands in more than he bargained for"--